Distracting Through Procedural Pain and Distress Using Virtual Reality and Guided Imagery in Pediatric, Adolescent, and Young Adult Patients: Randomized Controlled Trial - Jennifer A Hoag; Jeffrey Karst; Kristin Bingen; Akasha Palou-Torres; Ke Yan (JMIR Publications, 2022)
BackgroundChildren with acute and chronic illness undergo frequent, painful, and distressing procedures. ObjectiveThis randomized controlled trial was used to evaluate the effectiveness of guided imagery (GI) versus virtual reality (VR) on the procedural pain and state anxiety of children and young adults undergoing unsedated procedures. We explored the role of trait anxiety and pain catastrophizing in intervention response. MethodsChildren and young adults were recruited from the hematology, oncology, and blood and marrow transplant clinics at a children's hospital. Each study participant completed the GI and VR intervention during separate but consecutive unsedated procedures. Self-report measures of pain and anxiety were completed before and after the procedures. ResultsA total of 50 participants (median age 13 years) completed both interventions. GI and VR performed similarly in the management of procedural pain. Those with high pain catastrophizing reported experiencing less nervousness about pain during procedures that used VR than those using GI. State anxiety declined pre- to postprocedure in both interventions; however, the decrease reached the level of significance during the VR intervention only. Those with high trait anxiety had less pain during GI. ConclusionsIn our sample, VR worked as well as GI to manage the pain and distress associated with common procedures experienced by children with acute or chronic illnesses. Children who are primed for pain based on beliefs about pain or because of their history of chronic pain had a better response to VR. GI was a better intervention for those with high trait anxiety. Trial RegistrationClinicalTrials.gov NCT04892160; https://clinicaltrials.gov/ct2/show/NCT04892160